2014
DOI: 10.1016/j.ymssp.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven and adaptive statistical residual evaluation for fault detection with an automotive application

Abstract: An important step in model-based fault detection is residual evaluation, where residuals are evaluated with the aim to detect changes in their behavior caused by faults. To handle residuals subject to time-varying uncertainties and disturbances, which indeed are present in practice, a novel statistical residual evaluation approach is presented. The main contribution is to base the residual evaluation on an explicit comparison of the probability distribution of the residual, estimated online using current data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 58 publications
(116 reference statements)
0
15
0
Order By: Relevance
“…Model-based methods are typically used if mathematical models of the process and faults are available, whereas data-driven methods use historical data of complex systems to determine occurring faults, see, e.g., [24]. Although complex, the drilling process is limited in size and can be divided into two subsystems separated by the drill bit.…”
Section: Model-based Fault Detection and Isolationmentioning
confidence: 99%
“…Model-based methods are typically used if mathematical models of the process and faults are available, whereas data-driven methods use historical data of complex systems to determine occurring faults, see, e.g., [24]. Although complex, the drilling process is limited in size and can be divided into two subsystems separated by the drill bit.…”
Section: Model-based Fault Detection and Isolationmentioning
confidence: 99%
“…Such methods were covered in the survey by [31] and a study of data driven diagnosis showed design for isolability of different types of faults in automotive engines [32]. The same authors suggested an explicit comparison of the probability distribution of the residual, estimated online using current data, with no-fault residual distributions in [33] and found that tiny faults, i.e. also incipient ones, could be diagnosed in conditions where traditional methods would fall short.…”
Section: Detection Behaviour For Incipient Faultsmentioning
confidence: 99%
“…p fi = p NF . The Kullback-Leibler divergence itself has also been used as a hypothesis test for fault detection in, for example, (Zeng et al, 2014;Svärd et al, 2014) and (Bittencourt et al, 2014). An interesting analysis of the Kullback-Leibler divergence using the Neyman-Pearson lemma is found in (Eguchi and Copas, 2006).…”
Section: Distinguishabilitymentioning
confidence: 99%